A Clinical Mentorship and Quality Improvement Program to Support Health Center Nurses Manage Type 2 Diabetes in Rural Rwanda. (3rd December 2017) - Ndayisaba, Aphrodis; Harerimana, Emmanuel; Borg, Ryan; Miller, Ann C.; Kirk, Catherine M.; Hann, Katrina; Hirschhorn, Lisa R.; Manzi, Anatole; Ngoga, Gedeon; Dusabeyezu, Symaque; Mutumbira, Cadet; Mpunga, Tharcisse; et al.
Abstract : Introduction . The prevalence of diabetes mellitus is rapidly rising in SSA. Interventions are needed to support the decentralization of services to improve and expand access to care. We describe a clinical mentorship and quality improvement program that connected nurse mentors with nurse mentees to support the decentralization of type 2 diabetes care in rural Rwanda. Methods . This is a descriptive study. Routinely collected data from patients with type 2 diabetes cared for at rural health center NCD clinics between January 1, 2013 and December 31, 2015, were extracted from EMR system. Data collected as part of the clinical mentorship program were extracted from an electronic database. Summary statistics are reported. Results . The patient population reflects the rural settings, with low rates of traditional NCD risk factors: 5.6% of patients were current smokers, 11.0% were current consumers of alcohol, and 11.9% were obese. Of 263 observed nurse mentee-patient encounters, mentor and mentee agreed on diagnosis 94.4% of the time. Similarly, agreement levels were high for medication, laboratory exam, and follow-up plans, at 86.3%, 87.1%, and 92.4%, respectively. Conclusion . Nurses that receive mentorship can adhere to a type 2 diabetes treatment protocol in rural Rwanda primary health care settings.